DIGITAL TRANSFORMATION OF THE FINANCIAL ARCHITECTURE OF INCLUSIVE TERRITORIAL DEVELOPMENT: MECHANISMS FOR VETERAN REINTEGRATION AND POST-WAR RECOVERY OF UKRAINE - Anna Ivanova (Eastern Europe: Economy, Business and Management, 2026)
The article examines the theoretical and applied aspects of developing a digital financial ecosystem for inclusive territorial development amid digitalization, decentralization, and Ukraine’s post-war recovery. It is substantiated that growing socio-economic challenges, the expanding role of local self-government, and the need to support the social and economic reintegration of war veterans require modernizing approaches to financing territorial development. The study finds that the financial capacity of territorial communities provides the basis for implementing inclusive development policies and delivering quality public services. Despite the adverse effects of the full-scale war, Ukraine’s local finance system has maintained financial resilience, while local budget revenue and expenditure dynamics indicate a strengthening social orientation of fiscal policy. Particular attention is given to expenditures classified as “Social Protection of War and Labor Veterans,” which demonstrate a substantial increase in resources allocated to veterans’ policy and highlight the growing role of communities in veterans’ reintegration. It is argued that expanding financial support requires digital technology, integrated information systems, and performanceoriented public financial management. The role of Open Budget, eData, Prozorro, DREAM, and the Diia ecosystem in enhancing transparency, accountability, efficiency, and citizen participation is substantiated. The integration of financial resources, digital platforms, institutional mechanisms, and analytical tools into a unified digital environment creates conditions for more efficient public spending, stronger financial inclusion, and evidence-based local decision-making. Conceptual approaches to a digital financial ecosystem for inclusive territorial development are proposed based on inclusiveness, digital accessibility, transparency, accountability, adaptability, effectiveness, and participatory governance. Their implementation is expected to strengthen community financial capacity, improve local public financial management, enhance the targeting of social support, facilitate veterans’ reintegration, and support sustainable and inclusive territorial development during Ukraine’s post-war reconstruction.